واقع الصحافة الرياضية في ظل المشهد الإعلامي والرياضي المعاصر. - بوحيلة, رضوان (جامعة الوادي - University of Eloued, 2019)
إن خضوع الصحافة الرياضية لتأثيرات المنطق السلعي في الرياضة ولمنطق الفرجة في الإعلام جعلها تساهم بصورة مباشرة أو غير مباشرة في تغييب الطابع الأخلاقي عن الرياضة، وفي ظل التطور التكنولوجي في مجال الإتصال( وسائلا وتقنيات ونظم وشبكات )، وسيطرة المصالح المالية على عالم الرياضة: ممارسة وتنظيما وتغطية، إزداد التحدي على القائمين على الصحافة الرياضية المطبوعة من أجل الحفاظ على مكتسباتها الفنية والمهنية وتطويرها لمواكبة تحديات العالم الإفتراضي والرقمي، وإعادة النظر وتصحيح ما أمكن من مخرجاتالمشهد الإعلامي و الرياضي المعاصر من الإنحرافات التي أملتها سلبيات هيمنة الأمر الواقع المادي والتكنولوجي على مختلف جوانب الحياة المعاصرة. The Reality of Sports Journalism in the Contemporary Media and Sports Scene. Abstract: The subordination of sports journalism to the effects of commodity logic in sports and to the logic of watching the media, has contributed directly or indirectly to the de-moralization of sport, and under the technological evolution in the field of communication (means, technologies, systems, networks),and the control of financial interests over the world of sport: practice, organization and coverage,The challenge has been increased for the editors of the printed sports press, in order to preserve their technical and professional earnings and develop them to keeping up with the bets of the world's virtual and digital, and to reconsider and correct as much as possible the outputs ofcontemporary media and sports scene, from the deviations that were dictated by the negatives of the dominance of the material and technological de facto dominance on various aspects of contemporary life.
The Reality of Sports Journalism in the Contemporary Media and Sports Scene.
مقال
Keywords: الصحافة الرياضية، الرياضة، الإعلام المعاصر.; Sports journalism, Sport, Modern Media, Professional Pressures, Futures Bets